(untitled) (Web of Teachers: Inderscience Research, 2025)
This article investigates the reform of vocational education in Uzbekistan, focusing on new opportunities emerging from recent government initiatives and international best practices. It analyzes existing challenges, including curriculum obsolescence, insufficient digital integration, and weak industry collaboration, which contribute to suboptimal graduate employment rates. Through a comparative review of foreign and domestic experiences, the study highlights effective strategies such as competency-based curricula, enhanced public-private partnerships, and digitalization efforts outlined in Presidential Decree No. UP-5645. The article offers a multidimensional approach, combining policy analysis and empirical data, to propose actionable recommendations for modernizing vocational education. These reforms are critical for developing a skilled workforce that supports Uzbekistan’s sustainable economic growth and global competitiveness.